A Simulation Study on the Climate-Adaptive Design of Jiangmen Binjiang Sports Center. Issue 5 (March 2019) - Tian, Yu
Abstract: Jiangmen Binjiang Sports Center, is the representative of the sports buildings in the sub-tropical area of China. The research is exploring a low-carbon climate adaptive design strategy for sports buildings in the sub-tropics through a case study on whether the design strategy of the Jiangmen Binjiang Sports Center fits in with the sub-tropical climate by means of computer simulation of wind, light and heat of the building.